Antimicrobial effect of different physical and chemical compounds of zinc oxide and graphene oxide added to composite resins - Zohre Farhangian; Homayoon Alaghehmand; Hamed Tashakkorian; Faraneh Mokhtarpour; Abolfazl Davoodabadi (Wolters Kluwer Medknow Publications, 2022)
Background: Graphene oxide (GO), a product of graphite, is a candidate for nano-reinforcing cement-based materials due to its good water dispersibility and excellent mechanical properties. On the other hand, zinc oxide (ZnO) is well-known for its antibacterial characteristics as well. Therefore, we aimed to evaluate the impacts of adding ZnO and GO nanoparticles on the antibacterial properties of flowable composites. Materials and Methods: In this, in vitro experimental study was designated into five groups containing: (1) no nanoparticles as control group, (2) 1 wt.% ZnO nanoparticle, (3) 1 wt.% GO, (4) 1 wt.% physical compound of ZnO and GO, and (5) 1 wt.% chemical compound of ZnO and GO. The antibacterial properties of composite resin discs were evaluated by direct contact test. Data were analyzed using a one-way analysis of variance, followed by Tukey's post hoc tests (P = 0.05). Results: Streptococcus mutans colony counting in the first 24 h showed the least growth rate in the chemical compound group (2.2 × 10[5]). However, in 7 days, the least colony number was observed in the GO group (2 × 10[3]). Moreover, the physical compound showed the least bacterial adhesion. Conclusion: Adding GO alone to composites, compared to adding ZnO or physical and chemical compounds of GO-ZnO, was more helpful to increase the antimicrobial characteristics.